DAMPAK KUALITAS PELAYANAN PAJAK, PEMAHAMAN PAJAK, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM - Juliedt Bunga Andarista; Diana Airawaty (JURNAL ILMIAH EDUNOMIKA, 2026)
This study was conducted to determine the effect of tax service quality, tax understanding, and tax sanctions on MSME taxpayer compliance in Slahung District, Ponorogo for the 2021-2024 period. The population in this study were all MSME taxpayers in Slahung District, Ponorogo Regency, East Java. The analysis tool used was SPSS. SPSS output shows that tax service quality has a coefficient value of 0.111 with a significance value of 0.304, so this variable does not have a significant effect on MSME taxpayer compliance. The Effect of Tax Understanding (X2) on MSME Taxpayer Compliance (Y), the tax understanding variable shows a coefficient value of 0.324 with a significance value of 0.005, so it can be concluded that tax understanding has a significant and positive effect on taxpayer compliance. This finding also indicates that tax literacy remains a key factor driving MSME compliance. The Effect of Tax Sanctions (X3) on MSME Taxpayer Compliance (Y), based on a t-test, tax sanctions obtained a coefficient of 0.049 with a significance value of 0.667, thus having no significant effect on MSME taxpayer compliance. This condition indicates that existing sanctions have not provided a strong enough deterrent effect for taxpayers, or their implementation is not directly felt by some MSME actors.